Evaluating the Syllabus of ELT Research and Testing with CIPP Model - Kafle, Durga (Kanakai Journal, 2023)
The study aims to discuss the effectiveness and appropriateness of the ELT Research and Testing course of the M.Ed. program, third semester, major in English. The research is based on an interpretive paradigm. The method is narrative inquiry. Three students, who had completed the course and three teachers who have been teaching the course, were interviewed with open-ended questions. From the brief discussion, it was found that the course offers excellent and smart ideas based on the research as well as English language teaching.